Calorimetric analysis of the interplay between synthetic Tn antigen-presenting MUC1 glycopeptides and human macrophage galactose-type lectin - Beckwith, Donella M; FitzGerald, Forrest G.; Rodriguez Benavente, Maria C.; Mercer, Elizabeth R.; Ludwig, Anna-Kristin; Michalak, Malwina; Kaltner, Herbert; Kopitz, Jürgen; Gabius, Hans-Joachim; Cudic, Maré (Biochemistry, 2021)
Human macrophage galactose-type lectin (hMGL, HML, CD301, CLEC10A), a C-type lectin expressed by dendritic cells and macrophages, is a receptor for N-acetylgalactosamine alpha-linked to serine/threonine residues (Tn antigen, CD175) and its alpha 2,6-sialylated derivative (sTn, CD175s). Because these two epitopes are among malignant cell glycan displays, particularly when presented by mucin-1 (MUC1), assessing the influence of the site and frequency of glycosylation on lectin recognition will identify determinants governing this interplay. Thus, chemical synthesis of the tandem-repeat O-glycan acceptor region of MUC1 and site-specific threonine glycosylation in all permutations were carried out. Isothermal titration calorimetry (ITC) analysis of the binding of hMGL to this library of MUC1 glycopeptides revealed an enthalpy-driven process and an affinity enhancement of an order of magnitude with an increasing glycan count from 6-8 mu M for monoglycosylated peptides to 0.6 mu M for triglycosylated peptide. ITC measurements performed in D2O permitted further exploration of the solvation dynamics during binding. A shift in enthalpy-entropy compensation and contact position-specific effects with the likely involvement of the peptide surroundings were detected. KinITC analysis revealed a prolonged lifetime of the lectin-glycan complex with increasing glycan valency and with a change in the solvent to D2O.